The Effectiveness of CBT Group Counseling Using Cognitive Restructuring Techniques to Improve Student Resilience at Labschhol UNTAD High School in Palu - Dongalemba, Jullio Bey Christo; Hasan, Hasan; Rasido, Ikhlas; Nurwahyuni, Nurwahyuni (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study was conducted to determine the effectiveness of Cognitive Behavior Therapy (CBT) group counseling using cognitive restructuring techniques in improving the resilience of students at Labschool UNTAD Palu High School. This study was based on the low ability of students to cope with academic and non-academic pressures or challenges, which indicates a low level of resilience. This study used a quantitative pretest-posttest control group design approach. There were 20 students participating in the study, divided into two groups: an experimental group and a control group. The research instrument used a resilience scale that had been tested for validity and reliability. Data analysis used a paired sample t-test to determine the difference in resilience levels before and after treatment. The results showed a significant increase in student resilience levels after participating in group counseling using cognitive restructuring techniques. It is known that the average resilience score of the experimental group increased from 97.00 to 112.50 with a significance level (p) of 0.000 < 0.05. Thus, it can be concluded that CBT group counseling using cognitive restructuring techniques is effective in increasing the resilience of students at Labschool UNTAD Palu High School